MENJAGA KEARIFAN LOKAL DENGAN MEMBUDAYAKAN TRADISI BASUNTING BAGI MARAPULAI DALAM ADAT PERKAWINAN DI KANAGARIAN INDERAPURA KECAMATAN PANCUNG SOAL KABUPATEN PESISIR SELATAN - febrina khairunnisa (JURNAL ILMU BUDAYA, 2020)
This research is motivated by the unique tradition of a wedding or baralek party in Kanagarian Inderapura, Pancung Soal Subdistrict, Pesisir Selatan District, in Kanagarian Inderapura, the bridegroom or bridegroom starts to use suntiang as a bride in Minangkabau. This article was written to describe the tradition of basuntiang for marapulai in customary marriages in Kanagarian Inderapura, Pancung Soal Subdistrict, Pesisir Selatan District. The benefits of writing this article are expected to be able to provide more knowledge of the marital traditions that exist in the South Coastal District. The research method used is descriptive qualitative research subjects are citizens of Kanagarian Inderapura, Savings of Pancung Problem in the South Coastal District of Pesisir. Data collection techniques through interviews. The result of this research is to preserve local wisdom by cultivating the tradition of basuntiang for marapulai in customary marriages in Kanagarian Inderapura, Pancung Soal Subdistrict, Pesisir Selatan District which is different from other regions in Minangkabau. In other areas marapakai mamakai saluak, but in the Nagari area Inderapura started using suntiang as a head covering when holding a wedding party. The use of suntiang the groom (marapulai) is a custom that has been passed down through generations and inherited from ancestors.